From Hazardous Waste to Valuable Raw Material: Hydrolysis of CCA‐treated Wood for the Production of Chemicals. Issue 5 (3rd April 2013) - Hakola, Maija; Kallioinen, Anne; Leskelä, Markku; Repo, Timo
<x xml:space="preserve">Abstract</x> Solid wood, metal finnish: Instead of burning waste wood treated with chromated copper arsenite (CCA) or disposing of it in landfills, the CCA‐treated wood can be used as a raw material for the production of chemicals. Catalytic or alkaline oxidation together with very mild sulfuric acid extraction produces an easily enzymatically hydrolyzable material. Usage as a raw material for the chemical industry in this manner demonstrates a sustainable and value‐added waste management process.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>